Enhanced autoimmunity, arthritis, and encephalomyelitis in mice with a reduced oxidative burst due to a mutation in the Ncf1 gene - Hultqvist, Malin (National Academy of Sciences, 2004)
The Ncf1 gene was recently identified as a strong regulator of severe arthritis in rat. This finding was surprising, because the disease-promoting allele mediated a lower level of reactive oxygen species in NADPH oxidase-expressing cells. We have now investigated a splice mutation of the Ncf1 gene in B10.Q mice, causing a truncated and nonfunctional Ncf1 protein. We found that the mutated Ncf1 led to a more severe and chronic relapsing collagen-induced arthritis. Enhanced IgG and delayed-type hypersensitivity responses against type II collagen were seen, indicating increased activity of autoreactive T cells. Interestingly, female Ncf1-mutated mice spontaneously developed severe arthritis during the postpartum period. The arthritis was accompanied by an increased antibody response to type II collagen, with the same fine specificity as in collagen-induced arthritis. The enhancing effect of the mutated Ncf1 could also be shown to be more general in that it enhanced myelin oligodendrocyte glycoprotein protein-induced experimental autoimmune encephalomyelitis, a model for multiple sclerosis. These results show that Ncf1, a gene important for oxidative burst, regulates the susceptibility and severity of both arthritis and encephalomyelitis and modulates, directly or indirectly, the level of T cell-dependent autoimmune responses.